Interviewing parental couples together: Interaction between gender and occupation beyond child’s birth weight - Amorim, M.; Alves, E.; Freitas, C. DE; Samorinha, C.; Silva, S. (European Congress of Qualitative Inquiry, 2018)
Challenging the under-representation of fathers in the literature about parenthood in sociotechnical environments, recent health studies have resorted more often to couple interviews. Undertaking qualitative health-related research with heterosexual couples raises several ethical and methodological challenges regarding data collection and analysis. However, there is a scarcity of both population-specific guidelines and literature grounded on researchers’ experiences in this field.